TANTANGAN BERKARIER SUMBER DAYA MANUSIA LOKAL DI INDUSTRI PERHOTELAN SANUR - Retno Juwita Sari (Jurnal Ilmiah Hospitality Management, 2019)
From the analysis, it is found that there were still many challenges experienced by local communities in exploiting job opportunities, such as the incompatibility between labor qualifications required by the tourism industry and the capacity of local communities. The lack of capacity of human resources resulted from the low quality of education, the lack of knowledge and skills in the tourism industry, especially the hospitality, and the attitude and behavior or work ethic of the local community itself. The success or failure of cooperative relationship between the company and its human resources is inseparable from the role of desa adat. The role of desa adat here is to provide job-related information required by the company to assist the prospective workforce to obtain a job. The tourism sector is expected to build motivation and increase work productivity for the community in order to encourage the growth of the economic sector.